Benthic biofilm structure and function under abrupt flow changes - Julie Anne Hope; Julia Kleinteich; Sabine Ulrike Gerbersdorf (PLoS ONE, 2025)
Sediment accumulation reduces the capacity of dammed systems worldwide, therefore understanding sediment stability and transport within a reservoir is fundamental for sustainable management. Fluctuating hydrodynamics can alter the physical disturbance exerted on the sediment bed and can lead to substantial resuspension of bottom sediments and benthic biofilms. Removal of the biofilm can drastically alter the biochemical environment in the bed, and its ability to stabilize underlying sediments as microphytobenthic and bacteria communities are removed. In this experiment, an 8-week long hydraulic flume experiment was conducted to examine the response, adaptation and functionality of biofilms exposed to abrupt increases in flow typical of flow managed systems. Water and resuspended sediment from an oligotrophic reservoir in Germany, were used to develop biofilms on inserted flume cartridges. Developed biofilms were haphazardly distributed across two flow treatments: high bed shear stress (0.7 Pa) or low bead shear stress (0.1 Pa) for 28 days. Biochemical changes and biostabilization potential (adhesiveness) were examined over this period. Microphytobenthic biomass and composition, bacterial community diversity and extracellular polymeric carbohydrates/proteins were all initially altered by the abrupt increase in flow as the biofilm was stripped away. Biochemical properties largely recovered by the end of the experimental period (28-days) with recovery time and the degree of re-establishment dependent on the initial biofilm condition. However, sediment beds exposed to higher flows remained less stable, suggesting this functional role of the biofilm may take longer to reestablish itself after periods of higher flow. Findings suggest flow management has the potential to alter biofilm development and highlight the importance of protein content and microphytobenthic biomass in the recovery of biostabilization, Microphytobenthic diversity and carbohydrate content had less influence in the recovery of biostabilization. The findings may be useful to reservoir managers to manipulate flow to allow stable benthic biofilms to improve water quality and/or reduce infilling.